Use of Selective Serotonin Reuptake Inhibitor and Midodrine in a Patient With Autonomic Instability 2/2 Compressive Squamous Cell Carcinoma and Pain. (12th January 2018) - Ball, Kyle; Vacek, Thomas P.
A rare cause of reflex syncope is metastatic cancers involving the head and neck. These can irritate the glossopharyngeal nerve and lead to glossopharyngeal neuralgia with associated syncope. This type of syncope is difficult to treat since it commonly involves both a vasodepressor and cardioinhibitory response, and typically requires removal of the irritative focus. We report a case of a 52-year-old male who presented from home with syncope. He endorsed a 5-week history of progressively worsened positional headaches and dramatic 40-pound weight loss with night sweats over 6 months. In the emergency department, his heart rate was noted to drop into the 20s with associated hypotension 60/31 mm Hg. Heart rate and blood pressure increased with intravenous atropine. Physical examination revealed a large ulcerative lesion in the left tonsillar area. After biopsy of the lesion, a diagnosis of stage IV squamous cell carcinoma of the neck was made; computed tomography angiogram and positron emission tomography/computed tomography confirmed involvement in the posterior tongue extending to the left palatine tonsil in addition to the left jugular chain. The patient was started on cisplatin and radiation therapy, but continued to have episodes of syncope associated with bradycardia and hypotension. After a failed trial of benztropine, the patient was started on sertraline and midodrine with resolution of syncope. This could be a potential treatment option in those with compressive mixed syncope who are not candidates for surgery or chemotherapy or are awaiting definitive treatment.